Stroke prevention – review of the latest reports - Kasperski, Radosław; Piekarska, Małgorzata; Pacek, Katarzyna; Pikulicka, Agata; Szulc, Izabela; Jedlina, Klaudia; Swacha, Weronika; Świercz, Kamila (Journal of Education, Health and Sport, 2023)
Introduction and purpose: According to WHO 15 million people suffer from stroke, one-third of which dies and the other one-third is permanently disabled. For this reason, this condition is a very important medical and social problem. It is one of the leading causes of death, after cardiovascular diseases and cancer. It is also one of the most common causes of disability in the adult population. The economic aspects are related not only to the costs of hospital treatment, but above all to rehabilitation and chronic treatment. The aim of this article is to present the most important stroke risk factors and, based on them, to describe recommendations for effective stroke prevention. A brief description of the state of knowledge: In recent years, numerous studies have been conducted on the relationship between various factors and the risk of stroke. It turned out that many stroke risk factors are modifiable and by using various methods we are able to significantly reduce the risk of its occurrence. The most important risk factor is the patient's hypertension. Others are cardiovascular diseases such as atrial fibrillation; diabetes, obesity, low level of physical activity, improper diet, consumption of alcohol and tobacco products. Summary: Through education and promotion of a healthy lifestyle in society (high physical activity, healthy diet, lack of addictions, taking care of mental health and avoiding excessive stress), as well as regular blood pressure and glucose control and effective treatment of conditions leading to stroke, the incidence of stroke among people can actually be reduced. This issue still requires further research and constant expansion of our knowledge.